Kajian Yuridis tentang Penyandang Disabilitas - Dewi Krisna Hardjanti (Faculty of Law Hang Tuah University, 2016)
This research analyzes how the urgency Formation Draft Law of Persons with Disabilities, as a consequence of the ratification of the International Convention on the Rights of Persons with Disabilities and the Optional Protocol to the Convention Against (UN Resolution No. 61/1061 dated December 13, 2006) and set forth in Law No. 19 In 2011 on the Ratification of the International Convention on the rights of Persons with Disabilities. The use of the term disability have consequences on the paradigm shift that affects the approach to empowering people with disabilities. The research is normative juridist. The data obtained from primary legal materials, secondary and tertiary legal materials. The analysis is conducted qualitatively. Basing on the analysis concludes that the regulation of persons with disabilities in the legislation is very important. In addition because Indonesia is a country that has the goal of achieving prosperity, Indonesia also has an obligation to implement the convention on disability, other than the reality shows that the number of persons with disabilities each year is increasing. Therefore, as a form of government attention to persons with disabilities and as a consequence of the ratification of Convention on the Rights of Persons with Disabilities (CRPD), the government will issue a separate law governing persons with disabilities in all its aspects in accordance with the values of the philosophy of the Indonesian nation.